2018
DOI: 10.1111/gcb.14157
|View full text |Cite
|
Sign up to set email alerts
|

Ozone pollution will compromise efforts to increase global wheat production

Abstract: Introduction of high-performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal (SDG) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 206 publications
(137 citation statements)
references
References 60 publications
(147 reference statements)
4
133
0
Order By: Relevance
“…The EMEP MSC‐W (European Monitoring and Evaluation Programme, Meteorological Synthesising Centre‐West) chemical transport model (version 4.16, Simpson, Bergström, Imhof, & Wind, ; Simpson et al., ) was used to derive daily POD 3 IAM (phytotoxic ozone dose above 3 nmol m −2 s −1 , parameterized for integrated assessment modelling, CLRTAP, ) values for the years 2010 to 2012 per 1° by 1° grid cell as described by Mills, Sharps et al. (). POD 3 IAM is parameterized for a generic crop represented by wheat (CLRTAP, ) and represents the accumulated stomatal uptake of ozone, modelled from the hourly mean values for ozone, temperature, vapour pressure deficit, irradiance and soil moisture (Mills, Sharps et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EMEP MSC‐W (European Monitoring and Evaluation Programme, Meteorological Synthesising Centre‐West) chemical transport model (version 4.16, Simpson, Bergström, Imhof, & Wind, ; Simpson et al., ) was used to derive daily POD 3 IAM (phytotoxic ozone dose above 3 nmol m −2 s −1 , parameterized for integrated assessment modelling, CLRTAP, ) values for the years 2010 to 2012 per 1° by 1° grid cell as described by Mills, Sharps et al. (). POD 3 IAM is parameterized for a generic crop represented by wheat (CLRTAP, ) and represents the accumulated stomatal uptake of ozone, modelled from the hourly mean values for ozone, temperature, vapour pressure deficit, irradiance and soil moisture (Mills, Sharps et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst it is widely recognized that rapid breeding programmes will have a vital role to play in adaptations of crops to climate change (Atlin, Cairns, & Das, ), selection of traits for tolerance of one abiotic stress, tropospheric (ground level) ozone pollution, is currently omitted from such breeding programmes (Ainsworth, ; Frei, ). This is happening even though field experiments from nine countries representing three continents have shown that reducing ozone concentrations back to pre‐industrial levels would give an average wheat yield benefit of 8.4% globally (Pleijel, Broberg, Uddling, & Mills, ), a figure that is matched by modelling based on the stomatal uptake of the pollutant (Mills, Sharps et al., ). Furthermore, an earlier meta‐analysis of crop responses to ozone suggested that current ozone levels in the range 31–50 ppb (nmol/mol, v/v) are reducing the yield of major food crops by 5.3%–19% (Feng & Kobayashi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Avnery et al, 2011;Van Dingenen et al, 2009) or stomatal ozone uptake (e.g. Mills et al, 2018;Mills et al, submitted). For perennial vegetation, there is good representation of data in mid-latitudes of the Northern Hemisphere where grassland and forested areas provide grazing, harvestable biomass and other ecosystem services.…”
Section: Spatial Representativeness Of Analysismentioning
confidence: 99%
“…Many crops have been shown to be sensitive to ozone pollution, including staple foods such as rice (Akhtar et al, ), wheat (Wahid, ) and soybean (Betzelberger et al, ). Analysis of compiled data sets from many experiments has shown a wide range in ozone sensitivity between different crops, based on ozone concentration (Mills et al, ; Mills & Harmens, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ). Model‐based studies using dose‐response functions from such data sets have indicated potential crop yield reductions due to ozone across wide regions of the world (Avnery, Mauzerall, Liu, & Horowitz, ; Mills, Pleijel, et al, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ; Mills, Sharps, Simpson, Pleijel, Frei, et al, ; Van Dingenen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of compiled data sets from many experiments has shown a wide range in ozone sensitivity between different crops, based on ozone concentration (Mills et al, ; Mills & Harmens, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ). Model‐based studies using dose‐response functions from such data sets have indicated potential crop yield reductions due to ozone across wide regions of the world (Avnery, Mauzerall, Liu, & Horowitz, ; Mills, Pleijel, et al, ; Mills, Sharps, Simpson, Pleijel, Broberg, et al, ; Mills, Sharps, Simpson, Pleijel, Frei, et al, ; Van Dingenen et al, ). Experimental investigations have shown impacts of ambient ozone concentrations on a wide range of crop species in Europe and the USA by comparing responses of plants in filtered air to those in non‐filtered air (De Temmerman, Legrand, & Vandermeiren, ; Marzuoli, Finco, Chiesa, & Gerosa, ; Pleijel, Broberg, Uddling, & Mills, ).…”
Section: Introductionmentioning
confidence: 99%